2015
DOI: 10.1093/pcp/pcv056
|View full text |Cite
|
Sign up to set email alerts
|

Ubiquitin-Mediated Proteasomal Degradation of Oleosins is Involved in Oil Body Mobilization During Post-Germinative Seedling Growth in Arabidopsis

Abstract: In oleaginous seeds, lipids--stored in organelles called oil bodies (OBs)--are degraded post-germinatively to provide carbon and energy for seedling growth. To date, little is known about how OB coat proteins, known as oleosins, control OB dynamics during seed germination. Here, we demonstrated that the sequential proteolysis of the five Arabidopsis thaliana oleosins OLE1-OLE5 begins just prior to lipid degradation. Several post-translational modifications (e.g. phosphorylation and ubiquination) of oleosins we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
99
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 74 publications
(101 citation statements)
references
References 69 publications
2
99
0
Order By: Relevance
“…Determining whether such metabolic enzymes are K63 polyubiquitinated before reaching their destination or on site will require further investigation. The study of the plant oil body protein oleosin has revealed its complex ubiquitination pattern in sesame and Arabidopsis seeds (Hsiao & Tzen, 2011;Deruyffelaere et al, 2015). Oil bodies are seed-specific lipid droplets surrounded by a monolayer of amphiphatic lipids in which the structural protein oleosin is embedded.…”
Section: A Connection Between K63-linked Chains and Metabolismmentioning
confidence: 99%
See 1 more Smart Citation
“…Determining whether such metabolic enzymes are K63 polyubiquitinated before reaching their destination or on site will require further investigation. The study of the plant oil body protein oleosin has revealed its complex ubiquitination pattern in sesame and Arabidopsis seeds (Hsiao & Tzen, 2011;Deruyffelaere et al, 2015). Oil bodies are seed-specific lipid droplets surrounded by a monolayer of amphiphatic lipids in which the structural protein oleosin is embedded.…”
Section: A Connection Between K63-linked Chains and Metabolismmentioning
confidence: 99%
“…Oil bodies are degraded during germination to mobilize these energy reserves. At the onset of oil body mobilization, Arabidopsis oleosins can be conjugated to the mutually exclusive monoUb, K48-linked diUb or K63-linked diUb (Deruyffelaere et al, 2015). Proteasome inhibition by MG132 leads to the strong accumulation of K48-diubiquitinated oleosins in the cytosol, suggesting that oleosins are mostly degraded by the proteasome after extraction from oil bodies.…”
Section: A Connection Between K63-linked Chains and Metabolismmentioning
confidence: 99%
“…These Lys residues are, in addition to those immediately adjacent to the hairpin sequence, for presumed interactions with the phosphate groups of PLs on the LD surface. They could be the sites for ubiquitination, resulting in oleosin and thus LD degradation, which could occur during seed germination and seedling growth (Deruyffelaere et al, 2015). These Lys residues usually do not occur at specific positions along the sequences of diverse oleosins and, thus, do not represent evolutionary conservation.…”
Section: Oleosin Transcripts Are Present In Fruit Mesocarp Of Avocadomentioning
confidence: 99%
“…Phosphorylated perilipin interacts with lipase via a lipase moderator, a/b hydrolase domain-containing protein5, and binds to mitochondria via its C-terminal peptide; motifs in perilipin for these interactions are unknown (Wang et al, 2011). Conversely, oleosins could act only as a physical barrier preventing LDs from contacting lipase and glyoxysomes until germination and only after they have been phosphorylated or proteolyzed (Parthibane et al, 2012a;Deruyffelaere et al, 2015). Recently, a peanut oleosin (named OLE3 then and Arach.d-SL2 here) was shown to be a bifunctional enzyme exhibiting oleoyl-CoA:monoacylglycerol acyltransferase and phosphatidylcholine acylhydrolase (phospholipase) activities in transformed quadruple mutant yeast (Saccharomyces cerevisiae) in vivo or in isolated microsomes (Parthibane et al, 2012b).…”
Section: Oleosin Transcripts Are Present In Fruit Mesocarp Of Avocadomentioning
confidence: 99%
“…[2] The importance of FAs and the major metabolic end products of TAGs and membrane glycerolipids in terms of life activity have led to increased demand for them in food, chemical, and medical industries. Though several reviews have discussed advances in the field previously, [3,4] significant progress has been made in our understanding of lipid biosynthesis, transport, [5,6] storage, [7] degradation, [8] and transcriptional regulation. [9] With the aim of updating new findings, particularly those in lipid transport and transcription regulation for metabolic engineering, this article reviews and discusses transport and transcriptional regulation mechanisms that may hold keys and have great potential to be used for improvement of plant oil production and composition.…”
Section: Introductionmentioning
confidence: 99%